Ionizing Radiation Doses Detected at the Eye Level of the Primary Surgeon During Orthopaedic Procedures. Issue 7 (July 2016) - Cheriachan, Deepak; Hughes, Adrian M.; du Moulin, William S. M.; Williams, Christopher; Molnar, Robert
Abstract : Objectives: To evaluate the ionizing radiation dose received by the eyes of orthopaedic surgeons during various orthopaedic procedures. Secondary objective was to compare the ionizing radiation dose received between differing experience level. Design: Prospective comparative study between January 2013 and May 2014. Setting: Westmead Hospital, a Level 1 Trauma Centre for Greater Western Sydney. Participants: A total of 26 surgeons volunteered to participate within the study. Intervention: Experience level, procedure performed, fluoroscopy time, dose area product, total air kerma, and eye dose received was recorded. Participants were evaluated on procedure and experience level. Main Outcome Measurements: Radiation dose received at eye level by the primary surgeon during an orthopaedic procedure. Results: Data from a total of 131 cases was recorded and included for analysis. The mean radiation dose detected at the eye level of the primary surgeon was 0.02 mSv (SD = 0.05 mSv) per procedure. Radiation at eye level was only detected in 31 of the 131 cases. The highest registered dose for a single procedure was 0.31 mSv. Femoral nails and pelvic fixation procedures had a significantly higher mean dose received than other procedure groups (0.04 mSv (SD = 0.07 mSv) and 0.04 mSv (SD = 0.06 mSv), respectively). Comparing the eye doses received by orthopaedic consultants and trainees, there was no significant difference between the 2 groups. Conclusions: The risk of harmful levels of radiation exposure at eye level to orthopaedic surgeons is low. This risk is greatest during insertion of femoral intramedullary nails and pelvic fixation, and it is recommended that in these situations, surgeons take all reasonable precautions to minimize radiation dose. The orthopaedic trainees in this study were not subjected to higher doses of radiation than their consultant trainers. On the basis of these results, most of the orthopaedic surgeons remain well below the yearly radiation dose of 20 mSv as recommended by the International Commission on Radiological Protection.